Oxidative Stress and Bone Resorption Interplay as a Possible Trigger for Postmenopausal Osteoporosis. (12th January 2014) - Cervellati, Carlo; Bonaccorsi, Gloria; Cremonini, Eleonora; Romani, Arianna; Fila, Enrica; Castaldini, Maria Cristina; Ferrazzini, Stefania; Giganti, Melchiorre; Massari, Leo
Abstract : The underlying mechanism in postmenopausal osteoporosis (PO) is an imbalance between bone resorption and formation. This study was conducted to investigate whether oxidative stress (OxS) might have a role in this derangement of bone homeostasis. In a sample of 167 postmenopausal women, we found that increased serum levels of a lipid peroxidation marker, hydroperoxides, were negatively and independently associated with decreased bone mineral density (BMD) in total body (r = - 0.192, P < 0.05 ), lumbar spine (r = - 0.282, P < 0.01 ), and total hip (r = - 0.282, P < 0.05 ), as well as with increased bone resorption rate (r = 0.233, P < 0.05 ), as assessed by the serum concentration of C-terminal telopeptide of type I collagen (CTX-1). On the contrary, the OxS marker failed to be correlated with the serum levels of bone-specific alkaline phosphatase (BAP), that is, elective marker of bone formation. Importantly, multiple regression analysis revealed that hydroperoxides is a determinant factor for the statistical association between lumbar spine BMD and CTX-1 levels. Taken together, our data suggest that OxS might mediate, by enhancing bone resorption, the uncoupling of bone turnover that underlies PO development.